The interaction of focus, givenness, and prosody : a study of Italian clause structure - Samek-Lodovici, Vieri (New York : Oxford University Press, 2015)
An in-depth investigation of contrastive focalisation in Italian, showing that its syntactic expression systematically interacts with the syntactic expression of discourse-given phrases.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on October 8, 2015).
Keywords: Italian language -- Clauses; Perspective (Linguistics); Italian language -- Versification